Implementasi Prinsip Good Governance Bisnis Syariah pada Tata Kelola Manajer Investasi - Aang Anzal Muhammad Gofar; Gemala Dewi (Al Maal: Journal of Islamic Economics and Banking, 2021)
Investment Manager (MI) as a sharia mutual fund manager is done in two ways are the establishment of Sharia MI and Sharia Investment Management Unit (UPIS) for conventional MI. Most of conventional MI is not ready to spin off to become a Sharia MI because it is considered the current governance of MI is still low. OJK issued regulation No. 10/POJK.04/2018 on the Implementation of Investment Manager Governance that applies to both. However, the arrangement is still general and has not led to sharia governance system, while Indonesia has good governance guidelines for Sharia Business Governance (GGBS) that can be used as a reference standard. Based on these issues, the author reviewed the principles of GGBS to the extent of their implementation in the regulation of investment manager governance. This research is normative juridical with an analytical descriptive approach. Based on the results of the study the authors found that the governance arrangements of investment managers have not been sufficiently the basis for the implementation of sharia governance because principle of Independence has not been implemented for the ban on multiple positions for the Sharia Supervisory Board and spin off mechanisms for UPIS.